2013
DOI: 10.1002/jclp.22069
|View full text |Cite
|
Sign up to set email alerts
|

The “Vicissitudes of Love” Between Therapist and Patient: A Review of the Research on Romantic and Sexual Feelings, Thoughts, and Behaviors in Psychotherapy

Abstract: Beginning with Freud's observations in the early 1900 s, therapists' and patients' experiences of romantic and sexual reactions to each other during the course of therapy has been a topic that has generated alternating waves of avoidance and intense discussion in the professional literature. Research in the area flourished in the 1980s and 1990 s but then nearly disappeared with very little integration. We offer a review of the research to date. Although we focus primarily on quantitative studies, we also refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Empirically identifying whether or not there are relationships between clinician professional misconduct and personal and professional demographics is necessary to better understand types and contexts of professional misconduct in order to effectively and efficiently educate, develop, and supervise clinicians (Coy et al, 2016;Evan & Robinson, 2013). Moreover, since systematic studies of clinician gender and misconduct, particularly with regard to marriage and family therapists, are virtually non-existent, current research into this topic is needed to better understand professional misconduct as it actually occurs (Sonne & Jochai, 2014).…”
Section: The Relationship Of Clinician Demographic Variables To Discimentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically identifying whether or not there are relationships between clinician professional misconduct and personal and professional demographics is necessary to better understand types and contexts of professional misconduct in order to effectively and efficiently educate, develop, and supervise clinicians (Coy et al, 2016;Evan & Robinson, 2013). Moreover, since systematic studies of clinician gender and misconduct, particularly with regard to marriage and family therapists, are virtually non-existent, current research into this topic is needed to better understand professional misconduct as it actually occurs (Sonne & Jochai, 2014).…”
Section: The Relationship Of Clinician Demographic Variables To Discimentioning
confidence: 99%
“…While much research was conducted in the 1980s and 1990s with regard to clinician gender and professional sexual misconduct (Sonne & Jochai, 2014), there is a scarcity of current research on the topic of the clinician characteristics that appear to be coincident with various types of professional misconduct. The most current studies, while dated, have been based on: (a) case studies of clinicians who received treatment subsequent to sexual misconduct with a client (Celenza & Hilsenroth, 1997;Gabbard, 1994); (b) self-report questionnaires regarding misconduct (Garrett, 1999;Gartrell et al, 1986;Thoreson et al, 1993); and (c) analysis of complaints lodged with regulators and professional organizations (Grenyer & Lewis, 2012;Symons, 2011).…”
Section: Forty Years Sincementioning
confidence: 99%
“…As has been reviewed, the APA Ethics Code (APA, ) addresses each of these circumstances in enforceable standards that prohibit the first two under all circumstances and allows only for the later type of multiple relationships in certain rare circumstances. As will be reviewed below and described in detail by Sonne (), each of these types of multiple relationships brings with them significant potential for exploitation, abuse of trust and dependence, and inevitable harm to the client or former client.…”
Section: Boundaries and Multiple Relationshipsmentioning
confidence: 99%
“…It is not uncommon for psychotherapists to have sexual feelings for a client. Previous studies have shown prevalence rates for sexual attraction toward clients ranging from 60% to 90% and around a quarter of therapists have had sexual fantasies about a client (Garrett & Davis, 1998; Ladany et al, 1997; Pope et al, 1986, p. 40, 1987; Pope & Tabachnick, 1993; Rodolfa et al, 1994; Sonne & Jochai, 2014). In this context, such sexual or also romantic attraction of the therapist might be considered as erotic countertransference (Gabbard, 1994).…”
Section: Introductionmentioning
confidence: 99%